A Spotty Liver of Pregnancy - Meagan Gray MD; Don C. Rockey MD (SAGE Publishing, 2014)
Herpes simplex virus (HSV) hepatitis by definition constitutes disseminated herpes simplex infection; it is rare, with only approximately 130 cases reported in the literature. Although HSV hepatitis typically occurs in immunocompromised hosts, pregnancy-especially the third trimester, has been identified as a risk factor for its development. This is likely because of the fact that humoral and cell-mediated immunity decrease throughout pregnancy and nadir in the third trimester with decreased T-cell counts and altered B/T lymphocyte ratios. Here, we report on a patient with HSV 2 hepatitis in a previously healthy 27-year-old woman in her 23rd week of pregnancy. She initially presented with nausea, vomiting, and abdominal pain and was found to have acute hepatocellular liver injury and a systemic inflammatory response syndrome. Broad-spectrum antibiotics and acyclovir were promptly initiated. Liver biopsy, serum DNA polymerase chain reaction (PCR) as well as a labial ulcer culture and PCR were all positive for HSV 2. The patient recovered completely; however, her fetus did not survive. Review of the literature emphasizes that presentation with disseminated HSV infection typically occurs in the third trimester of pregnancy. This report emphasizes that abdominal pain combined with fever and hepatic dysfunction in pregnancy should prompt immediate consideration of the diagnosis of HSV hepatitis. Furthermore, given the high mortality rate and effective treatment, empiric treatment with acyclovir should be considered early in all potential cases.